MENGUSAHAKAN KEBAHAGIAAN DALAM KEGIATAN KERJA - Paulus Wahana (Jurnal Filsafat "WISDOM", 2017)
Work is a typical human activity that can only be performed by humans. As it is a conscious activity, its purposes and results require understanding. Work is an activity with certain purposes and results which are expected. Those expected purposes and results of work are certainly valuable for human lives. When the valueable aspects of expected purpose are actualised into reality, it will certainly create satisfaction or happiness, as the accompanying value that comes along with it, for individuals who work for it (bonum delectabile). In order to enable activities of work creating happiness in this life, then we need to be aware of the existence of values that can be materialized in work activities. Work therefore will no longer be seen as burdensome and exhaustive human practise in this life. Rather, it will be perceived as a way to materialise the values of life. By exploring and searching for the values which are contained in work, and then struggling for the embodiment these values, it is expected that the embodiment values of life can be maximised. Of course, the embodiment values of life which are being fought for as the expected purpose of work activities will bring happiness in this life.